Construction and validation of a risk prediction model for 3- and 5-year new-onset atrial fibrillation in HFpEF patients - Wang, Shuaishuai; Xie, Zhonglei; Wang, Fengjiao; Zhang, Wenzhong (Frontiers in Cardiovascular Medicine, 2024)
Background: Heart failure with preserved ejection fraction (HFpEF) patients are more prone to atrial fibrillation compared to heart failure with reduced ejection fraction (HFrEF). Nevertheless, the risk prediction model for new-onset atrial fibrillation (NOAF) in HFpEF patients remains a notable gap. Especially the neglect of imaging indicators. Methods: We retrospectively analyzed 402 HFpEF subjects reviewed in the Affiliated Hospital of Qingdao University from 2017 to 2023. We carried Cox regression analysis to screen predictors of new-onset atrial fibrillation ( NOAF ) . A nomogram was constructed based on these factors and internally validated through the bootstrap resampling method. The performance comparison between the nomogram and mC2HEST score was performed. Results: 62 (15%) of the 402 participants developed atrial fibrillation. Risk factors for NOAF were finally screened out to include Age, COPD, Hyperthyroidism, Renal dysfunction, LAD, and PASP, all of these were identified to create the nomogram. We calculated the bootstrap-corrected C-index (0.819,95%CI:0.762-0.870) and drew ROC curves (3-year AUC=0.827, 5-year AUC=0.825), calibration curves, and clinical decision curves to evaluate the discrimination, calibration, and clinical adaptability of the six-factor nomogram. Based on two cut-off values calculated by X-tile software, the moderate-, high-risk group had more NOAF than the low-risk group (P<0.0001). Our nomogram showed better 3-and 5-year NOAF predictive performance than mC2HEST score estimated by IDI and NRI (P<0.05).